Metal cutting theory and practice / David A Stephenson; John S Agapiou - Stephenson, David A.1959-
With updated information on machine tools, cutting tool material, and workholding technologies, this book offers selection criteria needed to identify the proper machine tool and tool materials for quality and cost effectiveness.